La aplicación de las reglas para conceder el habeas corpus a mujeres embarazadas que se encuentran cumpliendo sentencia ejecutoriada y el derecho de igualdad y no discriminación. - Almeida Bravo, Mario Francisco (2024)
This research examines the application of the Habeas Corpus rules established in Sentence No. 365-18-JH by the Constitutional Court, specifically regarding pregnant women serving criminal sentences, and how the conviction process conflicts with the rights to equality and non-discrimination. This qualitative study utilized theoretical research to gather insights from diverse sources, aiding in the identification of the legal characteristics of the issue. A doctrinal, legal, and historical analysis was conducted to establish these traits. The research also incorporated input from freelance legal professionals specializing in criminal and constitutional law, whose expert perspectives were crucial in shaping the study’s findings. Data was collected through surveys, leading to a comprehensive academic document containing reliable, evidence based information that addressed the scientific problem. Conclusions suggest that the rules issued by the Constitutional Court focus more on the seriousness of the crime of the Habeas Corpus petitioner rather than on whether the individual's right to life is in real and present danger.